Sex in television serials : understanding the influence on youths in Singapore - Koh, Melissa (2016)
The discourse on the effects of the television on youths have always revolved around media violence and sex in general. However, this study will attempt to extend previous research to focus on specifically television serials and its perceived effects in the sexual attitudes and behaviours of youths in Singapore. From the analysis of the various respondents, it is apparent that there is a positive relationship between the influence of sexual content in television serials and the sexual attitudes and behaviours of Singaporean youths. Using sexual socialisation to frame and analyse the findings, this study has also uncovered several themes such as desensitisation and the differences within different societies which are possible variables in establishing the extent of the relationship.